Re-entry Adjustment and Job Embeddedness: The Mediating Role of Professional Identity in Indonesian Returnees - Andrianto, Sonny; Jianhong, Ma; Hommey, Confidence; Damayanti, Devi; Wahyuni, Honey (Frontiers in Psychology, 2018)
The present study examined the relationship between difficulty in re-entry adjustment and job embeddedness, considering the mediating role of sense of professional identity. The online data on demographic characteristics, difficulty on re-entry adjustment, sense of professional identity, and job embeddedness were collected from 178 Indonesian returnees from multiple organizations. The results showed that difficulty in re-entry adjustment was a significant predictor of a sense of professional identity; a sense of professional identity was a significant predictor of job embeddedness. Furthermore, sense of professional identity is an effective mediating variable, bridging the relationship between post-return conditions to the home country and work atmosphere. Finally, the key finding of this study was that sense of professional identity mediated the effect of difficulty in re-entry adjustment on job embeddedness. The theoretical and practical implications, study limitations, and future research needs of our findings are noted.